Nanotechnology assisted biomarker analysis to rehabilitate acute ischemic stroke patients by early detection. (March 2022) - He, Jiangen; Jin, Shasha; Fan, Weijiao; Wu, Liang; Gopinath, Subash C.B.; Hu, Zhiwei
Highlights: Ischemic stroke leads the disruption of oxygen and nutrients supply to the brain. Early identification of stroke is for rehabilitation with reducing complications. Currently Magnetic resonance imaging and computed tomography are in use. Blood-based biomarker to identify at earlier stage helps to get precise conclusion. Discussed blood biomarkers for stroke & diagnosis by nanotechnology. Abstract: Ischemic stroke is the second highest global cause for disability, due to the reduction or interruption of blood flow to the part of brain. This leads the disruption of oxygen and nutrients supply to the brain tissue and makes the damage or dying to the brain cells. Early identification of stroke is possible for the rehabilitation with reducing the damage of the brain and avoids other complications. At the same time identifying the stroke at its acute phase is still challenging. Currently various imaging methods such as Magnetic resonance imaging and computed tomography are in use to predict and analyze the condition of stroke by cross section imaging of brain and head. However, accurate identification of stoke is questionable by these imaging techniques. So that, along with imaging, additional blood-based biomarker analysis to identify the stroke at earlier stage helps to get a precise conclusion on the medical status of the patient. This review has discussed on blood biomarkers for determining stroke and diagnosis by nanotechnology implemented biosensors towards the rehabilitation of acute ischemic stroke patients.